Massonia citrina (Hyacinthaceae, Hyacinthoideae)—a new species from the Western Cape Province (South Africa) - Pinter, Michael; Brudermann, Andreas; Crespo, Manuel B.; Deutsch, Gerfried; Martínez-Azorín, Mario; Müller-Doblies, Ute; Müller-Doblies, Dietrich; Pfosser, Martin; Wetschnig, Wolfgang (Phytotaxa, 2013)
In the course of a taxonomic revision of the genus Massonia Houtt., Massonia citrina M.Pinter, Deutsch, U.Müll.- Doblies & D.Müll.-Doblies, a new species of this genus from the Western Cape Province (South Africa), is here described. This species is similar to members of the M. depressa group, but it can be easily distinguished by its yellow filaments and style and the longer perigone-filament tube. A complete morphological description of the new species is presented.